2023
DOI: 10.1093/mnras/stad1319
|View full text |Cite
|
Sign up to set email alerts
|

Two warm Neptunes transiting HIP 9618 revealed by TESS and Cheops

Abstract: HIP 9618 (HD 12572, TOI-1471, TIC 306263608) is a bright (G = 9.0 mag) solar analogue. TESS photometry revealed the star to have two candidate planets with radii of 3.9 ± 0.044 R⊕ (HIP 9618 b) and 3.343 ± 0.039 R⊕ (HIP 9618 c). While the 20.77291 d period of HIP 9618 b was measured unambiguously, HIP 9618 c showed only two transits separated by a 680-d gap in the time series, leaving many possibilities for the period. To solve this issue, CHEOPS performed targeted photometry of period aliases to attempt to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…We demonstrated how CHEOPS can be used to followup TESS duotransits to expand the sample of long-period planets. Through the CHEOPS GTO Duos program, we have contributed to the discovery of 6 planets with orbital periods longer than 20 d, radii smaller than 5 R ⊕ , and host stars brighter than G = 12 mag (Osborn et al, 2022(Osborn et al, , 2023Tuson et al, 2023;Ulmer-Moll et al, 2023;Garai et al, 2023). There are only ∼ 18 other planets confirmed by TESS in this parameter space, illustrating the power of the TESS and CHEOPS synergy for the discovery of small, long-period planets transiting bright stars.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated how CHEOPS can be used to followup TESS duotransits to expand the sample of long-period planets. Through the CHEOPS GTO Duos program, we have contributed to the discovery of 6 planets with orbital periods longer than 20 d, radii smaller than 5 R ⊕ , and host stars brighter than G = 12 mag (Osborn et al, 2022(Osborn et al, , 2023Tuson et al, 2023;Ulmer-Moll et al, 2023;Garai et al, 2023). There are only ∼ 18 other planets confirmed by TESS in this parameter space, illustrating the power of the TESS and CHEOPS synergy for the discovery of small, long-period planets transiting bright stars.…”
Section: Discussionmentioning
confidence: 99%
“…However, in two cases, we measure only an upper limit on the planet mass. The first, HIP 9618 c, was externally validated and confirmed by Osborn et al (2023) using a combination of TESS and CHEOPS photometry and CAFE, HARPS-N, and SOPHIE RVs (see Section 10.6.2 for details). The second, TOI-554.02 (HD 25463 c) has not yet been confirmed, so we take additional measures to statistically validate this planet.…”
Section: Transit Searchmentioning
confidence: 98%
“…The TOI-669 Keck-NIRC2 observation was taken on 2019 June 9 using the K filter (λ 0 = 2.196 μm and Δλ = 0.336 μm) and an integration time of 10 s. The star appears single, and the Keck-NIRC2 observation rules out companions of Δ7.6 mag at 5σ confidence at a separation of 0 5. Osborn et al (2023) reported the discovery and confirmation of HIP 9618 b and c using space-based photometry from TESS and CHEOPS (Benz et al 2021) along with radial velocity observations from CAFE, HARPS-N, and SOPHIE (Perruchot et al 2008;Cosentino et al 2012;Aceituno et al 2013). To rule out dilution from nearby sources, the authors observed HIP 9618 with a variety of optical speckle and near-infrared (NIR) adaptive optics (AO) instruments, including Keck-NIRC2.…”
Section: Literature Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Somewhat surprisingly, the number of promising targets in our search area has increased very significantly in the past few years, and 6 out of 9 systems were discovered in 2021 or later. This rapidly increasing rate of discoveries can be devoted to the long observation time basis for planet search (e.g., repeated TESS visits) and the evolution of the observation strategies (e.g., follow-up long-period TESS planet candidates to determine the accurate period, (e.g., [122,[131][132][133]), which help the precise characterization of longperiod transiting planets. The chances of obtaining more and more appropriate candidates within the exomoon search region are increased due to the longer time coverage of the observations and also the better resolution of the full sky with appropriately long and precise observations (as indicated by the arrows in Figure 5.…”
Section: The Insufficiency Of the Catalogsmentioning
confidence: 99%